2018
DOI: 10.1080/08990220.2018.1484354
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory postural adjustments in the shoulder girdle in the reach movement performed in standing by post-stroke subjects

Abstract: After a stroke in middle cerebral artery territory, there is a high probability of dysfunction of the ventromedial pathways, mainly related with postural control mechanisms such as the anticipatory postural adjustments (APAs). According to neuroanatomical knowledge, these pathways have a predominant ipsilesional disposition, which justifies a bilateral postural control dysfunction, often neglected in rehabilitation. In order to assess this bilateral postural control dysfunction, electromyography activity was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…After suffering a stroke, there is an impairment in the cortico-spontine networks and an alteration in the information coming from the supplementary motor area, related to the temporal component of the APAs. This may be the reason why patients present a delay in the APAs ( 45 ) and alteration in normal movement patterns. In the scapula-humeral stabilizers this alteration results in worse stability and orientation of the shoulder and/or trunk during movement ( 46 ), generating excessive trunk displacement and decreased shoulder flexion and adduction along with reduced elbow extension (50).…”
Section: Discussionmentioning
confidence: 99%
“…After suffering a stroke, there is an impairment in the cortico-spontine networks and an alteration in the information coming from the supplementary motor area, related to the temporal component of the APAs. This may be the reason why patients present a delay in the APAs ( 45 ) and alteration in normal movement patterns. In the scapula-humeral stabilizers this alteration results in worse stability and orientation of the shoulder and/or trunk during movement ( 46 ), generating excessive trunk displacement and decreased shoulder flexion and adduction along with reduced elbow extension (50).…”
Section: Discussionmentioning
confidence: 99%
“…However, these associations and their meanings are not well established [ 83 ]. Similarly, and also for these variables, the role of FES application in the ipsilesional side should be considered, as according to our knowledge, no study has considered the impairments already demonstrated in the ipsilesional side in stroke patients in the application of FES [ 8 , 9 , 115 ]. The metrics that should be considered to assess the influence of FES in movement quality indicators are summarized in Figure 5 .…”
Section: Fes Usability In Post-stroke Patientsmentioning
confidence: 99%
“…It was estimated that after stroke, 70% of the patients present upper limb (UL) dysfunction, more than half present moderate to severe dysfunction, 40% are left with a non-functional arm with implications in quality of life [ 3 , 4 ] and only 5–20% recover UL function completely [ 5 , 6 ]. Although the main deficits were described for the contralesional limb (limb contralateral to the lesioned hemisphere), more recent studies have described postural control deficits also in the ipsilesional limb (limb ipsilateral to the lesioned hemisphere) [ 7 , 8 , 9 ], which were demonstrated to interfere in the rehabilitation of contralesional UL function [ 7 ]. Considering the determinant role of UL during activities of daily living (ADL) [ 10 , 11 , 12 , 13 ], the rehabilitation of UL function, namely to improve the ability to reach and grasp, required in over 50% of ADLs [ 14 ], is a primary aim in stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%